SENSE OF PLACE PADA KAWASAN TAMAN TEPIAN MAHAKAM, SAMARINDA - Bleszynski, Tiffany Prananingrum; Widyastuti, Dyah Titisari (Jurnal Arsitektur dan Perencanaan (JUARA), 2018)
Qualitative research aims to find out the impression that people feel about the Mahakam Tepian Park Area through the Sense of Place component, so in city development it might become a 'good place' while maintaining its characteristics. The research methods are questionnaires and field observations. The results showed that gathering on weekends was the dominant activity carried out, while the Mahakam River and Pesut Monument became the most recognizable physical forms. The meaning of the biggest respondent describes the Mahakam Tepian Park as a place with beautiful scenery to dispel weary and recreation. Structuring the physical forms will support the activity thus creating a good sense of place for the overall Mahakam Tepian Park.